A Review of Skull Base Tumor Clinical Trials: Past Trends and Future Opportunities - Devaiah, Anand; Murchison, Charles (Journal of Neurological Surgery Part B: Skull Base, 2017)
Objective Tumors of the anterior and lateral skull base (TALSB) are relatively rare but can be devastating to patients. By examining trials focused on TALSB, we can characterize the studies that predominate and better understand current directions of study. This gives us a better understanding of future studies to pursue.Study Design This is a retrospective analysis.Settings We set skull base tumor clinical trials in the United States which are listed in ClinicalTrials.gov.Subjects and Methods We used the information available on ClinicalTrials.gov to identify trends in clinical trials studying sinonasal/anterior skull base (SNASB) tumors, vestibular schwannoma (VS), and pituitary tumors. The publication rate for these trials was examined using PubMed.gov.Results Of the 71 trials analyzed, 83% investigated treatments for pituitary tumors, 16% for VSs, and 1% for SNASB tumors. Drug studies comprised 90% of all trials, while 9% included radiation therapy in their treatment and 10% included and surgical component. Overall, 64% had their results published in a peer-reviewed journal.Conclusion Among TALSB clinical trials we analyzed, they are weighted heavily toward drug trials. Radiation therapy and surgery, common treatment modalities, are underrepresented in clinical trials. There is a gap between the trials conducted and the rate of reporting, with an emphasis on positive results.
Keywords: skull base tumor; clinical trials; ClinicalTrials.gov; sinonasal cancer; vestibular schwannoma; pituitary tumor